Polyamide-based composites for automotive applications - Nurjannah, Salim; Nurul Huda, Abu Bakar; Siti Maznah, Kabeb; Nurlin, Abu Samah (Nova Science Publishers, 2025)
Polyamide (PA), also referred to as Nylon, is one of the most significant engineering thermoplastic materials. Polyamide, known for its outstanding mechanical and physical properties, proved its application in the automotive sector. The lightweight design allows for the manufacturing of automobiles that consume less fuel. This chapter will focus on the use of polyamide composite in manufacturing automotive components. It will cover polymer structure, reinforcement and filler, processing technique, and future direction of polyamide composite. It will also review the use of polyamide, along with their composites reinforced with fiberglass and carbon fiber, focusing on their potential as alternative materials in the automotive industry. Previously, air intake manifolds for automobiles were constructed from metal, but recently these are commonly produced from 30-35% glass-reinforced PA 6. Grades 6,6 and 4,6 are also utilized in manifolds. Replacing metal with nylon in the manifolds decreases production expenses by up to 30%, lowers the part's weight by up to 50%, reduces system costs by integrating parts, and enhances fuel efficiency